Promoting oral production through the task-based learning approach: a study in a public secondary school in colombia (2009)
Spoken language is used less confidently by learners in the English as a foreign language (efl ) classroom in secondary schools, and this has become a challenge for most teachers. This article describes an action research experience carried out at Francisco de Paula Santander, a public school in Bogotá, in 2004. The study was developed with a sample of learners belonging to four groups of seven graders along nine months. Data were collected by means of audio recordings, field notes and proformas. The results of the study let us analyze the different demands of transactional and interactional activities among novice efl speakers. They can also be considered an attempt to understand the implications of such activities within the framework of the Task-Based Learning approach presented by Willis (1996). Key words: Oral interaction, Task-Based Learning (tbl) Los estudiantes de los colegios de secundaria usan con menos seguridad el lenguaje oral en las clases de inglés como lengua extranjera y esto se ha constituido en un reto para muchos profesores. Este artículo describe una experiencia de investigación acción adelantada en el colegio público Francisco de Paula Santander en Bogotá, en el año 2004. El estudio se realizó con una muestra de estudiantes pertenecientes a cuatro cursos de séptimo grado, a lo largo de nueve meses. Los datos se recolectaron mediante grabaciones de audio, notas de campo y proformas. Los resultados del estudio nos permiten analizar las exigencias diferenciadas de las actividades interaccionales y transaccionales para hablantes novatos del inglés como lengua extranjera. También se pueden considerar como un intento por comprender las implicaciones de dichas actividades en el marco del enfoque de aprendizaje basado en tareas, presentado por Willis (1996). Palabras clave: Interacción oral, aprendizaje basado en tareas